Evaluation of Common and Atypical Clinical Presentations of Tinea Faciei: A Cross-sectional Study from Barabanki, Uttar Pradesh, India - Suganita; Deepika Agarwal; Sonal Sachan; Vandana Yadav; Harshit Jaiswal; Divya Prajapati (Journal of Clinical and Diagnostic Research)
Introduction: Tinea faciei is a dermatophytic infection affecting the glabrous skin of the face. While it is less common than dermatophyte infections of other anatomical sites, tinea faciei has become more prevalent in recent years, being reported in Dermatology Outpatient Departments. Aim: To enrich our understanding of tinea faciei with the intention of improving diagnostic accuracy and treatment outcomes. Materials and Methods: The present cross-sectional study was conducted in the Department of Dermatology, Venereology and Leprosy, Hind Institute of Medical Sciences, Barabanki, Uttar Pradesh, India, from October 2022 to October 2023. Total 75 patients with the clinical diagnosis of tinea faciei were recruited and subjected to Potassium Hydroxide (KOH) preparation for direct microscopic examination. Epidemiological data, as well as, information on exposure to systemic and oral steroids, and previous treatment was collected. Different morphologies of tinea faciei, involved site on the face, severity of itching, and additional affected body areas were also noted. Coding, data entry, clearing and compiling were done in Microsoft Excel sheets, and statistical software including Statistical Package for the Social Sciences (SPSS) software version 29.0 was used for statistical analysis. Results: The present study comprised 45 (60%) males and 30 (40%) females, with a mean age of 30.7 years. A total of 27 (36%) patients had pets at their homes, and 35 (46.6%) patients were involved in handling domestic animals. A family history was positive in 21 (28%) patients. The most common site in the face was the cheeks, affecting 45 (60%) patients, followed by areas around the eyes and nose in 26 (34.6%) patients each, the forehead in 23 (30.6%), and around the mouth and on the external ear in 22 (29.3%) patients each. The initial index lesion involving the face was found in 34 (45.3%) patients, while other sites were involved in 41 (54.6%) patients. The most common morphology included ill-defined margin, absence of scaling, the central clearing, pustular lesions, incomplete circle, psoriasiform and erosions. Steroid abuse was found in 73 (97.3%) patients, where most patients giving a history of only topical steroid usage. Conclusion: The present study offers important insights into various aspects of tinea faciei, including its occurrence, epidemiology, risk factors, and the role of steroid abuse. The authors have described various common and atypical clinical morphologies and distributions of tinea faciei and recognising these atypical signs can help clinicians diagnose the condition early and initiate timely treatment. Moreover, the present study highlights that many patients use steroids in the form of topical, oral and injection to get quick relief, which can complicate the diagnosis.